Assessment of Stabilizer Potential of Porang Flour and Maize Starch on Antioxidant Activity and Physicochemical Characteristics Ice Cream - Rofita, Rista Cahya; Ratmawati Malaka; Maruddin, Fatma (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2024)
Ice cream is a semi-frozen food made from milk or milk products, sweeteners, stabilizers, emulsifiers, and added flavors. Many ice cream product developments have been carried out to improve the quality of ice cream. One of them is the addition of stabilizers that maintain emulsions and enhance the softness of ice cream products. They can prevent the formation of large ice crystals in ice cream, provide uniformity of product texture, and provide resistance so that it does not melt easily. The purpose of this study was to analyze ice cream's antioxidant activity and physicochemical quality using different types and amounts of stabilizers (porang flour and cornstarch). This research method uses a completely randomized design (CRD) consisting of 5 levels of treatment with 3 replicates each. The treatment used in this study is the use of porang flour and cornstarch stabilizer at different concentrations, including; A1: 100% cornstarch; A2: Combination of 25% porang flour and 75% cornstarch; A3: Combination of 50% porang flour and 50% cornstarch; A4: Combination of 75% porang flour and 25% cornstarch; A5: 100% porang flour. The results showed that the treatment of the use of stabilizer combination of porang flour and cornstarch had a very significant effect (P<0.01) on ice cream testing parameters, including antioxidant activity and viscosity. Using a stabilizer combination of porang flour and cornstarch has no effect (P>0.05) on ice cream testing parameters, such as taste, texture, liking, melting power, and overrun. Treatment (A4) combines 75% porang flour and 25% cornstarch as stabilizers in ice cream. Keywords: Ice cream, stabilizer, antioxidant activity, physicochemical quality